Kanono refrakcija Antonios Susanos Byatt romane Apsėdimas - Rudaitytė, Regina (Literatūra, 2015)
The article focuses on the revision and transformation of the genre of romance, particularly in its 19th century poetical form, actualized in A. S. Byatt’s novel Possession through an enormous intertextual web of references. The major intertext in the novel is Victorian literature and culture on which Byatt concentrates, covering the whole romance canon through intertextual references to Romantic poetry and to the tradition of medieval romances in their Victorian rewritings. The play with the conventions of the genre of romance and its transformations, the pastiches of the Victorian poetry are the main narrative strategies for Byatt to achieve the refraction of the canon – a re-evaluation of the Victorian poetic tradition from the contemporary feminist and poststructuralist perspective.